ANALISIS SPASIAL TB PARU BTA POSITIF DI WILAYAH KERJA PUSKESMAS WUNA TAHUN 2015 - 2017 - Jumakil; Lymbran Tina; Eke Mahendra (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: One area with high rates of positive sputum in West Muna district, high TB patients is in the Wuna Community Health Center work area. Positive smear pulmonary TB sufferers in 2015 recorded 25 positive cases, in 2016 as many as 41 positive cases, whereas in 2017 there was an increase from the previous year which was 45 positive cases. Objective: To find out the distribution of cases tuberculosis with positive sputum from 2015 to 2017, then to be related to population density. Methods: This type of research is observational with spatio temporal modeling, based on geographic information systems. Results: There has been a shift in the pattern of positive pulmonary tuberculosis pulmonary TB sufferers from 2015 to 2017. TB cases in Maperaha, Nihi, Bungkolo villages have been concentrated in the same area for three years, as well as Waulai Village during 2016 and 2017. In Wuna Village. In 2015 and 2016 cases of tuberculosis were still concentrated around the same area, but differed in 2017, the concentration of cases shifted to the west. Conclusion: Cases of tuberculosis with positive sputum in the working area of Wuna Health Center from 2015-2017 have increased.